Physical, geotechnical and morphological characteristics of peat soils from Sarawak - Md. Aminur, Rahman; Kolay, Prabir K., Dr.; Siti Noor Linda, Taib, Dr.; Mohammad Ibrahim, Safawi, Assoc. Prof. Dr.; Ahmad Kamal, Abd Aziz (The Institution of Engineering, Malaysia (IEM), 2012)
Link to publisher's homepage at http://www.myiem.org.my/